The plight of women with cleft lips-A case report. - Mzezewa, Salathiel Zhou (Jour Med Resh and Health Sci, 2020)
Abstract. A 32year old mother of two presented to our out-patient department complaining that she was fed up of being taunted, for her lip deformity and that this has now resulted in divorce. She stated that when ever she meets new people or she attends gatherings, people stare at her and children laugh at her. She also complained that her children are taunted by other children for her deformity. She said the situation got worse a short while ago when her sisters in law taunted their brother (her husband) for marrying a wife with a cleft lip, leading to divorce. She was therefore requesting an operation to correct her deformity.